Polyhydroxyalkanoates for innovative electrodes and proton exchange membrane modification in microbial fuel cell / Sirajudeen Abdul Azeez Olayiwola - Sirajudeen, Abdul Azeez Olayiwola (2020)
The increase in global energy demand due to increasing population and industrialization demands renewable and environmental-friendly alternatives. Energy from fossil fuel are non-renewable, depleting and detrimental from environmental perspectives. Alternative energy, green and renewable such as hydrogen fuel, biodiesel, bioethanol, microbial fuel cell and many more have been extensively investigated. One possible solution lies with non-combustion method such as microbial fuel cell. A microbial fuel cell is a sustainable and environmental-friendly device that combines electricity generation and wastewater treatment through metabolic activities of microorganisms. However, low power output from inadequate electron transfer to the anode electrode hampers its practical implementation. Nanocomposite of oxidized carbon nanotubes and medium-chain-length polyhydroxyalkanoates (mcl-PHA) grafted with methyl acrylate monomers enhances anode-cathode electrodes electrochemical function in microbial fuel cell. Extensive polymerization of methyl acrylate monomers within mcl-PHA matrix, and homogenous dispersion of carbon nanotubes within the graft matrix are responsible for the enhancement. Modified electrodes exhibit high conductivities, enhanced redox peak and reduction of cell internal resistance up to 76 %. A stable voltage output at almost 700 mV running for 225 hours generating maximum power and current density of 351 mW/m2 and 765 mA/m2 respectively. Superior biofilm growth on modified anode surface as well as enhanced redox peak of modified cathode are responsible for improved electron transfer to the anode and efficient oxygen reduction rate at cathode, hence stable and elevated power output generation. Polyhydroxybutyrate (PHB) as an integrated component of ion exchange membrane in microbial fuel cell (MFC) was also investigated. PHB crystals ranging from 5-15 % (w/w) were thermally dispersed and composited within medium-chain-length polyhydroxyalkanoate (PHA) matrix as shown by spectroscopic analyses. The composite membranes were juxtaposed with Nafion membrane for improved ion conduction. Membrane with 10 % and 15 % (w/w) PHB recorded two-fold maximum voltage potential compared to Nafion membrane alone. A power density of 601 mW/m2 was recorded for PHB 15% membrane, which was superior to Nafion membrane (520 mW/m2). In operation with real wastewater, maximum voltage potential, water uptake, power and current densities, chemical oxygen demand (COD) removal, ammoniacal nitrogen (NH3-N) removal, as well as coulombic efficiency (CE) recovery of the composite membrane are superior to Nafion; attributed primarily to high resistivity to oxygen molecules diffusion from cathode to anode compartments, which subsequently improved the overall MFC performance.